Optimum configuration of a metal foam layer for a fast thermal charging energy storage unit: A numerical study. (April 2022) - Mehryan, S.A.M.; Ayoubloo, Kasra Ayoubi; Mahdavi, Mahboobe; Younis, Obai; Kazemi, Zahra; Ghodrat, Maryam; Ghalambaz, Mohammad
Highlights: A copper foam layer was used to enhance the melting heat transfer rate. Copper nanoparticles were also added to improve the thermal conductivity further. The size of the foam layer was considered fixed while its geometry could change. A mesh adaptation approach was applied to increase the accuracy of the phase change model. The volume fraction of nanoparticles and the shape of the foam layer were optimized. The results show that the porosity of the foam layer is the most crucial heat transfer factor. Abstract: The melting heat transfer of capric acid Phase Change Material (PCM) was numerically addressed in a channel shape Thermal Energy Storage (TES) unit. A combination of Cu nanoparticles and copper foam was used to improve the charging time of TES. A fixed amount of copper foam was applied to improve the heat transfer rate. The enthalpy-porosity approach, along with the finite element method, was used to simulate the free-convection melting heat transfer of composite PCM in the TES unit. Automatic time-step control and mesh adaptation technique were used to ensure the accuracy and convergence of the numerical solution. The porosity and the shape of the copper foam layer and volume fraction of nanoparticles were systematically optimized for minimum charging time using the Taguchi optimization approach. The results showed that a left right-hand triangle porous zone could lead to minimal charging time. The higher the porosity and volume fraction of nanoparticles, the lower the charging time. The combination of copper-foam, Cu nanoparticles, and optimum design of the porous layer reduced the melting time by three times. The optimal total charging time is reduced by 12.8% and 21.96% while changing the porous zone configuration from the RHT to REC and LHT.